The Lost Years 1918-1935 - Suluhian Kuyumjian, Rita (Կոմիտասի թանգարան-ին-տ. հրատ.)
The article covers the last 17 years of Komitas’s life. Constantinople Armenians who took care of Komitas, on the advice of Dr. Vahram Torkomian, seeing no improvement in Komitas’s mental health, while he was treated at Hopital de la Paix in Istanbul, decided to send him to Paris, hoping for better treatment and outcome. The article describes Komitas’s medical care, both psychiatric and physical until his death in 1935 when Komitas was in custodial care in Paris sanatoriums. It describes and analyses the findings from Komitas’s medical files at Ville- Evrard and Ville- Juif Hospitals. It reviews the psychiatric consultations, and explains the medical terms used at the beginning of the 20th century and its implications for psychiatric diagnosis used in Western psychiatry of today. Finally it describes his death due the bone infection in his foot and his funeral arrangements. Սույն հոդվածը նկարագրում է Կոմիտասի կյանքի և հիվանդության փարիզյան շրջանը մինչև իր մահը 1935 թ․ հոկտեմբերին։ 1918 թ. Զինադադարից հետո Կոմիտասի ընկերները բժիշկ Վահրամ Թորգոմյանի խորհրդով նրան բուժման նպատակով ուղարկում են Փարիզ։ Կոստանդնուպոլսի Լա Բե հիւանդանոցում Կոմիտասի առողջությունն անփոփոխ էր մնում, և լավացում չէր արձանագրվում։ Հոդվածն անդրադառնում է Փարիզի Վիլ Էվրար և Վիլ Ժուիֆ բուժական հաստատություններում Կոմիտասի բժշկական խնամքին։ Վերլուծության են ենթրկվում բժշկական թղթապանակը, բժշկական խորհրդատվությունները, համեմատվում են քսաներորդ դարասկզբին գործածված բժշկական ախտորոշիչ եզրույթները՝ ներկայիս գործածվող տարբերակների հետ։ Քննարկվում են նաև նրա ոտքի ոսկորի հիվանդությունն ու ֆիզիկական հյուծման պատճառով մահվան պարագան, ապա նաև թաղման կազմակերպումը։
Keywords: Classical musician